Explaining the Clustering of International Expansion Moves: A Critical Test in the U.S. Telecommunications Industry - Gimeno, Javier; Hoskisson, Robert E.; Beal, Brent D.; Wan, William P. (Academy of Management Journal, 2005)
This study distinguishes alternative competitive and institutional explanations of interorganizational mimicry by examining the clustering of U.S. telecommunications firms' 1995–95 moves into other Western Hemisphere countries. Mimicry of entry moves was more likely when both a focal firm and prior movers had large shares in the same domestic markets. More mimicry occurred among oligopolistic long-distance firms than among monopolistic local-exchange phone companies. Thus, mimetic international entry was strongly linked to the structure of domestic competition.